Infection status and molecular identification of digenean cercariae in snails in Kim Son district, Ninh Binh Province and Ba Vi district, Ha Noi - Doanh, Pham Ngoc; Hien, Hoang Van; Dung, Bui Thi; Loan, Ho Thi (Academia Journal of Biology, 2019)
In this study, the molecular method was used to identify digenean cercariae from freshwater snails in Kim Son District (Ninh Binh Province) and Ba Vi District Ha Noi. A total of 9 snail species were collected and examined for cercarial infection. Three snail species (Radix swinhoei, Angulyagra polyzonata and Pomacea canaliculata) were not infected, while the other 6 species (Austropeplea viridis, Gyraulus convexiusculus, Parafossarulus striatulus, Bithynia fuchsiana, Melanoides tuberculata and Tarebia granifera) were infected with digenean cercariae at low infection rates, ranging from 2.3% to 6.3%. Seven cercarial groups were identified: Echinostome, Monostome, Parapleurophocercaria, Xiphidiocercaria, Fucocercaria, Gymnocephalous and Megalurous. Snails M. tuberculata and P. striatulus were infected with 4 cercarial groups, A. viridis and G. convexiusculus snails were infected with 2 groups, 2 snail species B. fuchsiana and T. granifera were infected with one group of cercaria. The results of ITS2 sequences analyses of the cercarial groups identified the larvae of 9 trematode species, namely Echinostoma revolutum, Echinochasmus japonicus, Notocotylus intestinalis, Philophthalmus gralli, Haplorchis pumilio, Procerovum cheni, Fasciola gigantica, Australapatemon burti and Cyathocotyle prussica. Among them the last three species, P. cheni, A. burti and C. prussica, were found for the first time in Vietnam. In addition, the ITS-2 sequence of Gymnocephalous cercariae which was previously identified as Sphaeridiotrema monorchis, from P. striatulus snail was 97% similar to that of Sphaeridiotrema pseudoglobulus. Likewise, ITS-2 sequence of Echinostome cercaria from B. fuchsiana snail was 93% similar to that of E. japonicus and that of Xiphidiocercaria cercaria from M. tuberculata snail was 93% similar to Lecithodendrium spathulatum.